ValWorkBench: An open source Java library for cluster validation, with applications to microarray data analysis. Issue 2 (February 2015) - Giancarlo, R.; Scaturro, D.; Utro, F.
<x xml:space="preserve">Abstract</x> Highlights Cluster validation for microarray data analysis is an essential task in bioinformatics and biomedicine that is not receiving enough attention. The state of the art does not offer software systems able to help the development of much needed new measures. We propose ValWorkBench and describe its internal modules and classes, in order to provide the much needed software platform for the development and testing of new validation measures as well as clustering algorithms. From the programmer point of view, no other platform in the same area offers what ValWorkBench provides. From the user point of view, the measures contained in it have been the object of, rigorous scientific studies, i.e., in BMC Bioinformatics 9 (2008) 462; Algorithms for Molecular Biology 6 (2011) 1; Natural Computing, pages 2014 (in press).